Preparation method of graphene alloy electromagnetic shielding material

By generating alumina in situ on the surface of graphene and performing various modifications, the shortcomings of existing electromagnetic shielding coating materials in terms of electrical conductivity and durability are solved, and the electromagnetic shielding effect and dispersion of composite materials are significantly improved.

CN119410091AInactive Publication Date: 2025-02-11DONGGUAN YESHENG GRAPHITE TECH CO LTD

Patent Information

Application Number
CN202411723170.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing electromagnetic shielding coating materials have shortcomings in terms of electrical conductivity and durability, especially the lack of binding and dispersion of graphene in film-forming resins.

Method used

Alumina is generated in situ on the surface of graphene and modified with vinyl silane-containing coupling agent, glycidyl methacrylate, magnolol and cashewol, and modified acrylic resin in combination with p-hydroxycinnamol. , significantly improve the uniformity and compatibility of alumina/graphene in electromagnetic shielding material systems.

Benefits of technology

The electromagnetic shielding effect of the composite material is significantly improved, the dispersion and compatibility of alumina/graphene are enhanced, and its binding force in the film-forming resin is improved.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a preparation method of a graphene alloy electromagnetic shielding material, and belongs to the technical field of electromagnetic shielding materials. The preparation method of the graphene alloy electromagnetic shielding material comprises the following steps: mixing a reaction monomer, lauryl sodium sulfate, deionized water and an initiator, and carrying out polymerization reaction to obtain modified acrylic resin; the preparation method comprises the following steps: heating and mixing polyol and isocyanate, adding a chain extender and deionized water, and stirring and mixing to obtain waterborne polyurethane; and stirring the modified acrylic resin, the waterborne polyurethane, the modified filler and other auxiliaries at a high speed to obtain the water-based paint. The uniformity and compatibility of alumina / graphene in an electromagnetic shielding material system are remarkably improved through compound modification of multiple components, and then the electromagnetic shielding effect of the composite material is remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electromagnetic shielding materials and relates to a method for preparing a graphene alloy electromagnetic shielding material. Background Art

[0002] Electromagnetic shielding materials can effectively resist the intrusion of electromagnetic radiation in the environment on the signals of electronic products, ensuring that the signals of electronic products are real and stable; at the same time, it can also prevent electronic products from releasing electromagnetic radiation into the environment, thereby ensuring the signal safety of electronic products. As a fluid material, it has the advantages of simple preparation and low cost, and can be easily sprayed or brushed on the surface of various plastic products to form a conductive electromagnetic shielding layer to achieve the effect of electromagnetic wave shielding. It is widely used in electronic components, circuit board printing, construction, transportation, military, aerospace and other fields. The core element of electromagnetic shielding coatings lies in shielding fillers.

[0003] At present, electromagnetic shielding coating materials are mainly conductive coatings, and the added conductive fillers are usually metal particles such as gold, silver, copper, nickel, and non-metallic particles such as carbon black and graphite. Gold powder and silver powder are favored for their excellent conductivity and chemical stability, but their high prices limit their application. The performance of copper powder and nickel powder is close to that of silver, but they are easily oxidized, resulting in unstable conductivity and poor durability of the electromagnetic shielding coatings made from them. Carbon black and graphite powders, as conductive fillers, have good dispersibility and low prices, but are slightly insufficient in terms of conductivity.

[0004] Patent document CN201510896392.9 discloses a method for preparing an electromagnetic shielding coating. The method uses non-metallic parts as the application object, adopts graphene and conductive carbon black as functional fillers, and prepares a lightweight, long-lasting, serialized electromagnetic shielding coating material based on highly conductive graphene functional fillers. The method can not only effectively improve the electromagnetic protection capability of the equipment, but also meet the demand for lightweight equipment. However, the method only uses a surface modifier to modify the graphene, and the graphene lacks binding strength with film-forming resins such as acrylic resin or polyurethane resin, and the improvement in dispersibility is limited. Summary of the invention

[0005] The object of the present invention is to provide a method for preparing a graphene alloy electromagnetic shielding material. The present invention generates aluminum oxide in situ on the surface of graphene, modifies it by using a vinyl silane coupling agent, glycidyl methacrylate, magnolol and cardanol, and modifies the acrylic resin with p-hydroxycinnamyl alcohol. The uniformity and compatibility of aluminum oxide / graphene in the electromagnetic shielding material system are significantly improved through the composite modification of multiple components, thereby significantly improving the electromagnetic shielding effect of the composite material.

[0006] The purpose of the present invention can be achieved through the following technical solutions:

[0007] A method for preparing a graphene alloy electromagnetic shielding material comprises the following steps:

[0008] S1, mixing the reaction monomer, sodium dodecyl sulfate, deionized water and initiator and performing a polymerization reaction to obtain a modified acrylic resin;

[0009] S2, heating and mixing the polyol and isocyanate, adding a chain extender and deionized water, stirring and mixing, to obtain a waterborne polyurethane;

[0010] S3, after high-speed stirring the modified acrylic resin, waterborne polyurethane, modified filler and other additives, the product is obtained.

[0011] As a preferred technical solution of the present invention, in step S1, the polymerization reaction is a polymerization reaction at a temperature of 85-90°C for 2-3h; the mass ratio of the reaction monomer, sodium dodecyl sulfate, deionized water and initiator is 50-52:0.2-0.3:20-25:0.6-0.7; the reaction monomer is a mixture of methyl methacrylate, butyl acrylate, methacrylic acid and p-hydroxycinnamyl alcohol in a mass ratio of 35-40:18-24:3-5:0.5-0.7; and the initiator is initiator AIBA.

[0012] As a preferred technical solution of the present invention, in step S2, the heating mixing is mixing at a temperature of 80-85°C for 1.5-2.0h; the stirring mixing is stirring at a temperature of 72-78°C for 1.0-1.5h; the mass ratio of the polyol, isocyanate, chain extender and deionized water is 7.0-7.8:5.1-5.3:2.2-2.4:24-30.

[0013] As a preferred technical solution of the present invention, in step S2, the polyol is polytetrahydrofuran with a molecular weight of 2000; the isocyanate is MDI, i.e. 4,4-diphenylmethane diisocyanate; and the chain extender is ethylenediamine.

[0014] As a preferred technical solution of the present invention, in step S3, the high-speed stirring is stirring at a speed of 1000-1200 r / min for 30-40 min; the mass ratio of the modified acrylic resin, waterborne polyurethane, modified filler and other additives is 50-54:20-23:9-10:1.2-1.4.

[0015] As a preferred technical solution of the present invention, in step S3, the other additives are prepared by mixing a dispersant, a defoamer and a leveling agent in a mass ratio of 1.6-1.8:2.2-2.5:3.0-3.4; the dispersant is BYK-190; the defoamer is BYK-024; and the leveling agent is BYK-346.

[0016] The present invention discloses a method for preparing the modified filler, comprising the following steps:

[0017] Step 1: placing graphene, the mixed solution and pseudo-boehmite on a ball mill for ball milling, filtering out, placing in an oven for vacuum drying, and calcining to obtain a composite powder;

[0018] Step 2: placing the composite powder and anhydrous ethanol in a reaction kettle, stirring and mixing, preheating, adding a silane coupling agent, heating and stirring, centrifuging to obtain a solid, washing, placing in an oven for vacuum drying, and obtaining an intermediate;

[0019] Step 3: After ultrasonically mixing the intermediate and anhydrous ethanol, the composite monomer and initiator are added, heated and stirred, and the solid is taken out by centrifugation, washed, and placed in an oven for vacuum drying to obtain modified particles.

[0020] As a preferred technical solution of the present invention, in step one, the ball milling time is 30 minutes; the vacuum drying is drying at a temperature of 110°C to constant weight; the calcination is calcining at a temperature of 550-600°C for 5-6 hours; the mass ratio of the graphene, the mixed liquid and the pseudo-boehmite is 50-55:70-80:12-14: the mixed liquid is mixed by polyethylene glycol and anhydrous ethanol in a mass ratio of 3:1-1.2.

[0021] As a preferred technical solution of the present invention, in step 2, the stirring and mixing time is 20-30 minutes; the preheating treatment is heating to 40°C; the heating and stirring is stirring at 62-68°C for 5-6 hours; the cleaning is cleaning three times with anhydrous ethanol; the vacuum drying is vacuum drying at 80°C to constant weight; the mass ratio of the composite powder, anhydrous ethanol and silane coupling agent is 10-12:40-50:3.4-4.0; the silane coupling agent is a vinyl-containing silane coupling agent, and preferably, the silane coupling agent used in the scheme of the present invention is silane coupling agent A-171.

[0022] As a preferred technical solution of the present invention, in step three, the ultrasonic mixing is performed at a power of 160-200W for 8-10 minutes; the heating and stirring treatment is performed at a temperature of 70-76°C and a speed of 300-400r / min for 6-7 hours; the mass ratio of the intermediate, anhydrous ethanol, composite monomer and initiator is 8-10:30-40:1.6-2.0:0.07-0.08; the composite monomer is formed by mixing glycidyl methacrylate, magnolol and cardanol in a mass ratio of 1.2-1.5:1.8-2.0:1.4-1.8.

[0023] The invention discloses a graphene alloy electromagnetic shielding material prepared by the preparation method.

[0024] Beneficial effects of the present invention:

[0025] The present invention generates aluminum oxide in situ on the surface of graphene, modifies it by using a vinyl silane coupling agent, glycidyl methacrylate, magnolol and cardanol, and modifies acrylic resin with p-hydroxycinnamyl alcohol. The uniformity and compatibility of aluminum oxide / graphene in an electromagnetic shielding material system are significantly improved through composite modification of multiple components, thereby significantly improving the electromagnetic shielding effect of the composite material. DETAILED DESCRIPTION

[0026] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.

[0027] Example 1

[0028] A method for preparing a graphene alloy electromagnetic shielding material comprises the following steps:

[0029] S1. After mixing the reaction monomer, sodium dodecyl sulfate, deionized water and initiator, polymerize them at 85°C for 2 hours to obtain a modified acrylic resin; the mass ratio of the reaction monomer, sodium dodecyl sulfate, deionized water and initiator is 50:0.2:20:0.6; the reaction monomer is prepared by mixing methyl methacrylate, butyl acrylate, methacrylic acid and p-hydroxycinnamyl alcohol in a mass ratio of 35:18:3:0.5; the initiator is initiator AIBA.

[0030] S2. After mixing the polyol and isocyanate at 80°C for 1.5 hours, a chain extender and deionized water are added and stirred at 72°C for 1.0 hour to obtain a waterborne polyurethane; the mass ratio of the polyol, isocyanate, chain extender and deionized water is 7.0:5.1:2.2:24; the polyol is polytetrahydrofuran with a molecular weight of 2000; the isocyanate is MDI; and the chain extender is ethylenediamine.

[0031] S3. Stir the modified acrylic resin, waterborne polyurethane, modified filler and other additives at a speed of 1000 r / min for 30 minutes to obtain; the mass ratio of the modified acrylic resin, waterborne polyurethane, modified filler and other additives is 50:20:9:1.2; the other additives are prepared by mixing the dispersant, defoamer and leveling agent in a mass ratio of 1.6:2.2:3.0; the dispersant is BYK-190; the defoamer is BYK-024; and the leveling agent is BYK-346.

[0032] The preparation method of the modified filler comprises the following steps:

[0033] Step 1: placing graphene, a mixed solution and pseudo-boehmite on a ball mill for 30 minutes, filtering out, placing in an oven at 110° C. and vacuum drying to constant weight, and calcining at 550° C. for 5 hours to obtain a composite powder; the mass ratio of the graphene, the mixed solution and the pseudo-boehmite is 50:70:12: the mixed solution is prepared by mixing polyethylene glycol and anhydrous ethanol at a mass ratio of 3:1;

[0034] Step 2: Place the composite powder and anhydrous ethanol in a reaction kettle and stir for 20 minutes, then heat to 40°C, add a silane coupling agent and stir at 62°C for 5 hours, centrifuge to obtain a solid, wash it three times with anhydrous ethanol, place it in an oven at 80°C and vacuum dry it to constant weight to obtain an intermediate; the mass ratio of the composite powder, anhydrous ethanol and silane coupling agent is 10:40:3.4;

[0035] Step 3: After ultrasonicating the intermediate and anhydrous ethanol at a power of 160 W for 8 minutes, add the composite monomer and the initiator, stir at a temperature of 70°C and a speed of 300 r / min for 6 hours, centrifuge the solid, wash it, and place it in an oven for vacuum drying to obtain modified particles; the mass ratio of the intermediate, anhydrous ethanol, composite monomer and initiator is 8:30:1.6:0.07; the composite monomer is prepared by mixing glycidyl methacrylate, magnolol and cardanol in a mass ratio of 1.2:1.8:1.4.

[0036] Example 2

[0037] A method for preparing a graphene alloy electromagnetic shielding material comprises the following steps:

[0038] S1. After mixing the reaction monomer, sodium dodecyl sulfate, deionized water and initiator, polymerize them at 88°C for 2.5 hours to obtain a modified acrylic resin; the mass ratio of the reaction monomer, sodium dodecyl sulfate, deionized water and initiator is 51:0.25:22:0.65; the reaction monomer is prepared by mixing methyl methacrylate, butyl acrylate, methacrylic acid and p-hydroxycinnamyl alcohol in a mass ratio of 38:21:4:0.6; the initiator is initiator AIBA.

[0039] S2. After mixing the polyol and isocyanate at 82°C for 1.8 hours, a chain extender and deionized water are added and stirred at 75°C for 1.2 hours to obtain a waterborne polyurethane; the mass ratio of the polyol, isocyanate, chain extender and deionized water is 7.4:5.2:2.3:27; the polyol is polytetrahydrofuran with a molecular weight of 2000; the isocyanate is MDI; and the chain extender is ethylenediamine.

[0040] S3. Stir the modified acrylic resin, waterborne polyurethane, modified filler and other additives at a speed of 1100 r / min for 35 minutes to obtain; the mass ratio of the modified acrylic resin, waterborne polyurethane, modified filler and other additives is 52:22:9.5:1.3; the other additives are prepared by mixing dispersant, defoamer and leveling agent in a mass ratio of 1.7:2.4:3.2; the dispersant is BYK-190; the defoamer is BYK-024; and the leveling agent is BYK-346.

[0041] The preparation method of the modified filler comprises the following steps:

[0042] Step 1: placing graphene, a mixed solution and pseudo-boehmite on a ball mill for 30 minutes, filtering out, placing in an oven at 110° C. and vacuum drying to constant weight, and calcining at 575° C. for 5.5 hours to obtain a composite powder; the mass ratio of the graphene, the mixed solution and the pseudo-boehmite is 52:75:13; the mixed solution is prepared by mixing polyethylene glycol and anhydrous ethanol at a mass ratio of 3:1.1;

[0043] Step 2: Place the composite powder and anhydrous ethanol in a reaction kettle and stir for 25 minutes, then heat to 40°C, add a silane coupling agent and stir at 65°C for 5.5 hours, centrifuge to obtain a solid, wash it three times with anhydrous ethanol, place it in an oven at 80°C and vacuum dry it to constant weight to obtain an intermediate; the mass ratio of the composite powder, anhydrous ethanol and silane coupling agent is 11:45:3.7;

[0045] Step 3: After ultrasonicating the intermediate and anhydrous ethanol at a power of 180 W for 9 minutes, add the composite monomer and the initiator, stir at a temperature of 73° C. and a speed of 350 r / min for 6.5 hours, centrifuge the solid, wash it, and place it in an oven for vacuum drying to obtain modified particles; the mass ratio of the intermediate, anhydrous ethanol, composite monomer and initiator is 9:35:1.8:0.075; the composite monomer is prepared by mixing glycidyl methacrylate, magnolol and cardanol in a mass ratio of 1.4:1.9:1.6.

[0046] Example 3

[0047] A method for preparing a graphene alloy electromagnetic shielding material comprises the following steps:

[0048] S1. After mixing the reaction monomer, sodium dodecyl sulfate, deionized water and initiator, polymerize them at 90°C for 3 hours to obtain a modified acrylic resin; the mass ratio of the reaction monomer, sodium dodecyl sulfate, deionized water and initiator is 52:0.3:25:0.7; the reaction monomer is prepared by mixing methyl methacrylate, butyl acrylate, methacrylic acid and p-hydroxycinnamyl alcohol in a mass ratio of 40:24:5:0.7; the initiator is initiator AIBA.

[0049] S2. After mixing the polyol and isocyanate at 85°C for 2.0h, a chain extender and deionized water are added and stirred at 78°C for 1.5h to obtain a waterborne polyurethane; the mass ratio of the polyol, isocyanate, chain extender and deionized water is 7.8:5.3:2.4:30; the polyol is polytetrahydrofuran with a molecular weight of 2000; the isocyanate is MDI; and the chain extender is ethylenediamine.

[0050] S3. Stir the modified acrylic resin, waterborne polyurethane, modified filler and other additives at a speed of 1200 r / min for 40 minutes to obtain; the mass ratio of the modified acrylic resin, waterborne polyurethane, modified filler and other additives is 54:23:10:1.4; the other additives are prepared by mixing dispersant, defoamer and leveling agent in a mass ratio of 1.8:2.5:3.4; the dispersant is BYK-190; the defoamer is BYK-024; and the leveling agent is BYK-346.

[0051] The preparation method of the modified filler comprises the following steps:

[0052] Step 1: placing graphene, a mixed solution and pseudo-boehmite on a ball mill for 30 minutes, filtering out, placing in an oven at 110°C for vacuum drying to constant weight, and calcining at 600°C for 6 hours to obtain a composite powder; the mass ratio of the graphene, the mixed solution and the pseudo-boehmite is 55:80:14; the mixed solution is prepared by mixing polyethylene glycol and anhydrous ethanol at a mass ratio of 3:1.2;

[0053] Step 2: placing the composite powder and anhydrous ethanol in a reaction kettle and stirring for 30 minutes, heating to 40°C, adding a silane coupling agent and stirring at 68°C for 6 hours, centrifuging to obtain a solid, washing it three times with anhydrous ethanol, placing it in an oven at 80°C and vacuum drying it to constant weight to obtain an intermediate; the mass ratio of the composite powder, anhydrous ethanol and silane coupling agent is 12:50:4.0;

[0054] Step 3: After ultrasonicating the intermediate and anhydrous ethanol at a power of 200 W for 10 minutes, adding the composite monomer and the initiator, stirring at a temperature of 76° C. and a speed of 400 r / min for 7 hours, centrifuging the solid, washing it, and placing it in an oven for vacuum drying to obtain modified particles; the mass ratio of the intermediate, anhydrous ethanol, the composite monomer and the initiator is 10:40:2.0:0.08; the composite monomer is prepared by mixing glycidyl methacrylate, magnolol and cardanol in a mass ratio of 1.5:2.0:1.8.

[0055] Comparative Example 1

[0056] Compared with Example 3, the difference in Comparative Example 1 is that p-hydroxycinnamyl alcohol is not used, and the other components, preparation steps and parameters are the same.

[0057] Comparative Example 2

[0058] Compared with Example 3, Comparative Example 2 is different in that glycidyl methacrylate is not used, and the remaining components, preparation steps and parameters are the same.

[0059] Comparative Example 3

[0060] Compared with Example 3, the difference in Comparative Example 3 is that magnolol is not used, and the other components, preparation steps and parameters are the same.

[0061] Comparative Example 4

[0062] Compared with Example 3, Comparative Example 4 is different in that cardanol is not used, and the other components, preparation steps and parameters are the same.

[0063] Comparative Example 5

[0064] Compared with Example 3, the difference in Comparative Example 5 is that no silane coupling agent is used in step 2, and the other components, preparation steps and parameters are the same.

[0065] Comparative Example 6

[0066] Compared with Example 3, the difference in Comparative Example 6 is that graphene replaces the composite powder, and the other components, preparation steps and parameters are the same.

[0067] The samples prepared in Examples 1-3 and Comparative Examples 1-6 were subjected to the following performance tests, respectively, and the test results are shown in Table 1.

[0068] Heat resistance: GB / T 1735-2009, treated at 100℃ for 4h;

[0069] Shielding effectiveness: According to the provisions of GB / T 25471-2010, the coating thickness is 2mm;

[0070] Table 1

[0071] Shielding effectiveness (dB) Heat resistance Example 1 82 qualified Example 2 80 qualified Example 3 83 qualified Comparative Example 1 72 Small part of the foam Comparative Example 2 67 Small part of the foam Comparative Example 3 62 More foaming Comparative Example 4 64 Small part of the foam Comparative Example 5 59 More foaming Comparative Example 6 61 More foaming

[0072] From the test results in Table 1, it can be seen that compared with comparative examples 1-6, the electromagnetic shielding materials prepared in embodiments 1-3 of the present invention have higher shielding effectiveness and excellent electromagnetic shielding capabilities.

[0073] The present invention modifies acrylic resin by para-hydroxycinnamyl alcohol, introduces benzene ring structure and hydroxyl group, and increases compatibility and interface bonding strength between acrylic resin and waterborne polyurethane and modified filler; pseudo-boehmite is ground and combined with graphene, and after calcination, aluminum oxide is generated in situ on the surface of graphene, and agglomeration phenomenon caused by hydrogen bond of graphene itself is reduced; then, a vinyl-containing silane coupling agent is used to modify composite powder formed by aluminum oxide / graphene, and the introduced vinyl group participates in the copolymerization reaction between glycidyl methacrylate, magnolol and cardanol, thereby significantly improving the organic coating rate of the composite powder, increasing its hydrophobicity, effectively increasing the dispersibility of aluminum oxide / graphene in the electromagnetic shielding material system, and improving the electromagnetic shielding effect of the composite material; chemical grafting of glycidyl methacrylate is carried out, and the composite powder is obtained by the following steps: It has good compatibility with modified acrylic resin, and its epoxy group can form a covalent bond with isocyanate, which can increase the volume of aluminum oxide / graphene. Magnolia officinalis contains multiple vinyl groups that can increase the grafting rate of glycidyl methacrylate, and it contains multiple phenolic hydroxyl groups and benzene ring structures that can promote the compatibility and bonding between the composite powder and the modified acrylate and waterborne polyurethane. At the same time, the phenolic hydroxyl groups contained in cardanol promote the bonding strength of aluminum oxide / graphene in the system, and its carbon-carbon long chain can increase the fluidity of aluminum oxide / graphene in the system, avoiding excessive cross-linking to limit its dispersion uniformity. That is, the present invention significantly improves the uniformity and compatibility of aluminum oxide / graphene in the electromagnetic shielding material system through the compounding and modification of multiple components, thereby significantly improving the electromagnetic shielding effect of the composite material.

[0074] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A method for preparing a graphene alloy electromagnetic shielding material, characterized in that: The preparation method comprises the following steps: S1, mixing the reaction monomer, sodium lauryl sulfate, deionized water and initiator and performing a polymerization reaction to obtain a modified acrylic resin; S2, heating and mixing the polyol and isocyanate, adding a chain extender and deionized water, stirring and mixing, to obtain a waterborne polyurethane; S3, stirring the modified acrylic resin, waterborne polyurethane, modified filler and other additives at high speed to obtain; Wherein, the preparation method of the modified filler comprises the following steps: Step 1: placing graphene, the mixed solution and pseudo-boehmite on a ball mill for ball milling, filtering out, placing in an oven for vacuum drying, and calcining to obtain a composite powder; Step 2: placing the composite powder and anhydrous ethanol in a reaction kettle, stirring and mixing, preheating, adding a silane coupling agent, heating and stirring, centrifuging to obtain a solid, washing, placing in an oven for vacuum drying, and obtaining an intermediate; Step 3: After ultrasonically mixing the intermediate and anhydrous ethanol, the composite monomer and initiator are added, heated and stirred, and the solid is taken out by centrifugation, washed, and placed in an oven for vacuum drying to obtain modified particles.

2. The method for preparing a graphene alloy electromagnetic shielding material according to claim 1, characterized in that: In step S1, the polymerization reaction is carried out at a temperature of 85-90°C for 2-3h; the mass ratio of the reaction monomer, sodium dodecyl sulfate, deionized water and initiator is 50-52:0.2-0.3:20-25:0.6-0.7; the reaction monomer is a mixture of methyl methacrylate, butyl acrylate, methacrylic acid and p-hydroxycinnamyl alcohol in a mass ratio of 35-40:18-24:3-5:0.5-0.7; and the initiator is initiator AIBA.

3. The method for preparing a graphene alloy electromagnetic shielding material according to claim 1, characterized in that: In step S2, the heating mixing is mixing at a temperature of 80-85°C for 1.5-2.0h; the stirring mixing is stirring at a temperature of 72-78°C for 1.0-1.5h; the mass ratio of the polyol, isocyanate, chain extender and deionized water is 7.0-7.8:5.1-5.3:2.2-2.4:24-30.

4. The method for preparing a graphene alloy electromagnetic shielding material according to claim 1, characterized in that: In step S2, the polyol is polytetrahydrofuran with a molecular weight of 2000; the isocyanate is MDI; and the chain extender is ethylenediamine.

5. The method for preparing a graphene alloy electromagnetic shielding material according to claim 1, characterized in that: In step S3, the high-speed stirring is stirring at a speed of 1000-1200 r / min for 30-40 min; the mass ratio of the modified acrylic resin, waterborne polyurethane, modified filler and other additives is 50-54:20-23:9-10:1.2-1.

4.

6. The method for preparing a graphene alloy electromagnetic shielding material according to claim 1, characterized in that: In step S3, the other additives are prepared by mixing a dispersant, a defoamer and a leveling agent in a mass ratio of 1.6-1.8:2.2-2.5:3.0-3.

4.

7. The method for preparing a graphene alloy electromagnetic shielding material according to claim 1, characterized in that: In step one, the ball milling time is 30 minutes; the vacuum drying is performed at 110°C to constant weight; the calcination is performed at 550-600°C for 5-6 hours; the mass ratio of the graphene, the mixed solution and the pseudo-boehmite is 50-55:70-80:12-14: the mixed solution is prepared by mixing polyethylene glycol and anhydrous ethanol in a mass ratio of 3:1-1.

2.

8. The method for preparing a graphene alloy electromagnetic shielding material according to claim 1, characterized in that: In step 2, the stirring and mixing time is 20-30 minutes; the preheating treatment is heating to 40°C; the heating and stirring is stirring at 62-68°C for 5-6 hours; the cleaning is cleaning three times with anhydrous ethanol; the vacuum drying is vacuum drying at 80°C to constant weight; the mass ratio of the composite powder, anhydrous ethanol and silane coupling agent is 10-12:40-50:3.4-4.0; and the silane coupling agent is a vinyl-containing silane coupling agent.

9. The method for preparing a graphene alloy electromagnetic shielding material according to claim 1, characterized in that: In step three, the ultrasonic mixing is performed at a power of 160-200 W for 8-10 minutes; the heating stirring treatment is performed at a temperature of 70-76° C. and a speed of 300-400 r / min for 6-7 hours; the mass ratio of the intermediate, anhydrous ethanol, composite monomer and initiator is 8-10:30-40:1.6-2.0:0.07-0.08; the composite monomer is prepared by mixing glycidyl methacrylate, magnolol and cardanol in a mass ratio of 1.2-1.5:1.8-2.0:1.4-1.

8.

10. A graphene alloy electromagnetic shielding material prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Preparation method for electromagnetic shielding coating

    CN105505054A

Cited By

  • Wear-resistant silica gel ink and preparation method thereof

    CN120554892A